Reframing Health Promotion for People With Intellectual Disabilities. (10th April 2015) - Cardell, Beth
The World Health Organization calls for health promotion to expand beyond the health care system by considering social determinants of health, engaging multiple levels, targeting policy change, and including social action. This qualitative study embraces this holistic stance as a means to address the health disparities and inequities experienced by people with intellectual disabilities (ID) by supporting the development of interventions that consider components of social justice along with embracing this population's potential and acknowledging influences of the context. A content analysis of the data is presented to illustrate how an occupational viewpoint can promote positive health and well-being of people with ID. The four gerunds of Wilcock's Occupational Perspective on Health —doing, being, belonging, and becoming—are utilized and supported by the literature to offer actions that can be taken by health promotion professionals to address the health needs of people with ID.